Implementasi Pelayanan Penerbitan Akta Kelahiran Balita Menggunakan Klampid New Generation di Kelurahan Dupak - Frida Apprilia Pradini; Endik Hidayat (Public Inspiration : Jurnal Administrasi Publik, 2023)
One of the government's products in the field of population and civil registration is a birth certificate. A Birth Certificate is a valid proof issued by the Department of Population and Civil Registration no later than 60 (sixty) days after the birth event which contains the status and birth event of a child in a family which shows that the child is a legal citizen according to law. Ownership of birth certificates is considered less important for some residents because the issuance process is considered difficult and takes a long time. The purpose of this research is to find out how effective the service for issuing birth certificates is using the Klampid New Generation application at the Surabaya City Population and Civil Registration Service. The research was conducted using a descriptive qualitative approach using an inductive method. In collecting data, techniques of observation, documentation, and interviews were used. As for data analysis, the Data Reduction method, Data Presentation, and Conclusion Drawing were used. The results of this study are that the implementation of online birth certificate issuance services using Klampid New Generation at the Surabaya City Population and Civil Registration Service has been running effectively with the issuance of 3 (three) documents at once on 1 (one) application.